Changes in Parents’ Spanking and Reading as Mechanisms for Head Start Impacts on Children - Gershoff, Elizabeth T. (J Fam Psychol, 2015)
This study examined whether Head Start, the nation’s main two-generation program for low-income families, benefits children in part through positive changes in parents’ use of spanking and reading to children. Data were drawn from the 3-year-old cohort of the national evaluation of the Head Start program known as the Head Start Impact Study (N = 2,063). Results indicated that Head Start had small indirect effects on children’s spelling ability at age 4 and their aggression at age 4 through an increase in parents’ reading to their children. Taken together, the results suggest that parents plays a role in sustaining positive benefits of the Head Start program for children’s behavior and literacy skills, one that could be enhanced with a greater emphasis on parent involvement and education.